TOWARDS A THEORY OF LIBRARY VALUES: EXPLORING AND GIVING LIBRARY VALUES AS AN EFFORT TO IMPROVE THE IMPROVEMENT AND STRENGTHENING OF LIBRARY IMAGES IN A CULTURAL SOCIO PERSPECTIVE - BAKHTIYAR (CV KULTURA DIGITAL MEDIA, 2020)
Research intends to describe the values ​​contained in the library. The research object is a form of in-depth study, a detailed discussion of content management to explore and describe library values ​​as an effort to improve and strengthen the library's image. Research includes focusing on the realization of management achievement of improvement and strengthening of the library's image through the application of library values. Research is an analysis of the critical thinking of reality to the applicative conceptualization of historical developments that have taken place and are taking place, methodologically called a historical approach characterized by critically investigating the progress of a term or thought. Library research data search techniques, conducting a study of various reading materials, with subjects exploring, describing library values, enhancing, strengthening the image of the library and its application in various dimensions of librarianship. Analysis is carried out through qualitative descriptive analysis, which is analysis that departs from various studies, reviews of various library materials containing theoretical, research and non-research. Content analysis is used to analyze the meaning of the conceptualization of digging, describe the values ​​of the library and its application to the world of librarianship. Daily observations on library activities are empowered to support the construction of theory. The results of the study showed that the values ​​of the library had a very dominant influence on the image of the existence of the library as a public service institution.